Tokyo 2020: Evaluation of the elite sport expenditures and success in 14 nations - De Bosscher, V.; Shibli, S. (SPLISS, 2021)
The SPLISS Pillar 1 - Light Study evaluates the inputs and outputs of 14 nations in the Tokyo 2020 Olympics. Estimating how much nations spend on elite sport is a measure of input. The amount of success achieved, typically medal-based measures, represent the output of the system. The results of the study provide useful contemporary insight into the funding for elite sport, the outputs achieved and the relationship between the two measures.